2013
DOI: 10.2478/popore-2013-0002
|View full text |Cite
|
Sign up to set email alerts
|

Pygoscelid penguins breeding distribution and population trends at Lions Rump rookery, King George Island

Abstract: Long term changes (46 years) in the abundance of pygoscelid penguins breeding populations and nests distribution in the Lions Rump (King George Island) colony were in− vestigated in three time intervals, according to previously published two censuses and one original study conducted in 2010. At that time a detailed colony map based on the GIS system was made. Results of this study showed different trends for each investigated species. In the last three decades Adélie penguin breeding populations showed strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 30 publications
(40 reference statements)
5
17
0
Order By: Relevance
“…This result reflects the trends in populations from different localities on King George Island (e.g., Chwedorzewska and Korczak 2010;Korczak-Abshire et al 2013;Braun et al 2017;Sierakowski et al 2017;Znój et al 2017) as well as trends in the whole Antarctic Peninsula region (e.g., Hinke et al 2007;Lynch et al 2012;Lyver et al 2014). Moreover, some authors suggest that further reductions in the icedependent Adélies population are likely if the frequent climate anomalous events continue (Ainley et al 2010;Hinke et al 2017).…”
Section: Resultsmentioning
confidence: 59%
“…This result reflects the trends in populations from different localities on King George Island (e.g., Chwedorzewska and Korczak 2010;Korczak-Abshire et al 2013;Braun et al 2017;Sierakowski et al 2017;Znój et al 2017) as well as trends in the whole Antarctic Peninsula region (e.g., Hinke et al 2007;Lynch et al 2012;Lyver et al 2014). Moreover, some authors suggest that further reductions in the icedependent Adélies population are likely if the frequent climate anomalous events continue (Ainley et al 2010;Hinke et al 2017).…”
Section: Resultsmentioning
confidence: 59%
“…Periglacial and denudation processes began to modify the landscape, further increasing glacier ablation. The intensified surface melting provided increased freshwater discharge from glacial rivers and delivered more suspended material to the near shore environment of King George Island, all of which affected the local ecosystems [49,50]. Our study results demonstrated that new ice-free areas were added at different rates during different periods, which must be taken into account when studying the influence of environmental changes on the maritime and land ecosystems.…”
Section: Discussionmentioning
confidence: 86%
“…During that time, the Ad elie colony declined from a peak of roughly 9600 breeding pairs in 1988/1989 to a minimum of 2038 in 2012/2013, representing a nearly 79% decline in abundance. The magnitude of decline is commensurate with population trends at other Ad elie penguin colonies on King George Island (Sander et al 2007, Carlini et al 2009, Korczak-Abshire et al 2013) and throughout the northern Antarctic Peninsula region across a wide range of colony sizes (Lynch et al 2012).…”
Section: Study Sitementioning
confidence: 53%
“…, Korczak‐Abshire et al. ) and throughout the northern Antarctic Peninsula region across a wide range of colony sizes (Lynch et al. ).…”
Section: Methodsmentioning
confidence: 99%